Warunki skutecznego wdrażania koncepcji zarządzania wiedzą w organizacji - Czubasiewicz, Halina; Grajewski, Piotr (The Conditions of Effective Implementation Conception of Knowledge Management, 2006)
Management is knowledge in a modern manner fashionable trend in science about management. The article contains relating the influence of party of conception management the knowledge in enterprise on building individual his systems considerations. This concerns especially organizational system and personnel. Systems these have to support the disseminating of management the knowledge, creating the conditions for utilization of this idea to building the chances of marketable organizations. The management requires at organization with knowledge build in her in strategy of organization. From party and realization of strategy leaning on utilization the knowledge it depends the survival and development of present organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 147-153